Micro-offline gains do not reflect offline learning during early motor skill acquisition in humans - Anwesha Das; Alexandros Karagiorgis; Jörn Diedrichsen; Max-Philipp Stenner; Elena Azañón (Proceedings of the National Academy of Sciences, 2025)
While practicing a new motor skill, resting for a few seconds can improve performance immediately after the rest. This improvement, referred to as “micro-offline gains” (MOGs), has been interpreted as rapid offline learning and is thought to be supported by neural replay of the trained movement sequence during rest. Here, we provide evidence that MOGs reflect only transient performance benefits, partially mediated by motor planning, and not offline learning. In five experiments, participants trained to produce a sequence of finger movements as many times as possible. When participants trained during 10-s practice periods, interleaved with 10-s rest periods, they produced more correct keypresses during training than participants who trained continuously without taking breaks. However, this benefit vanished within seconds after training, when both groups performed under comparable conditions, revealing similar levels of skill acquisition. This challenges the idea that MOGs reflect offline learning, which, if present, should result in sustained performance benefits, compared to training without breaks. Furthermore, we observed persistent MOGs even when participants produced random, nonrepeating sequences, indicating that MOGs do not relate to the offline consolidation of a sequence-specific memory. Rather, sequence-specific learning was only evident online, during practice. Finally, MOGs were diminished when participants could not preplan the first few movements of an upcoming practice period. Our results suggest that MOG are simply an effect of slowing during practice, combined with the possibility of preplanning the initial movements after rest, and therefore do not serve as a reliable metric for offline learning or skill-related consolidation.